Correlation of absorbed impact with calculated strain energy using an instrumented Charpy impact test - Ali, Mohd Basri; Abdullah, Shahrum; Nuawi, Zaki; Ariffin, Ahmad Kamal (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2013)
This paper presents the correlation of impact energy obtained from the laboratory test as well as the calculated energy using the power spectrum density (PSD) method. Based on a previous study, the total absorbed energy obtained using the dial/encoder system may be significantly different, depending on the strength and the ductility of test specimen. For this reason, we determined the energy of the experimental system coming from the dial/encoder Charpy impact test using the signal processing approach. Strain gauges are connected between the Charpy impact striker and the high frequency data acquisition system in order to capture the dynamic impact strain response. A specimen of an aluminium alloy of 6061-T6 is used in the experiment, which is designed according to the ASTM E23. For the analysis an obtained signal is converted from the time domain to the frequency domain by means of PSD method and the area under its plot is used to calculate strain energy. The comparison between energy absorbed during the experiment and the strain energy is performed at different velocities and thicknesses. The total energy absorbed using the dial/encoder system can be linked by a polynomial equation with R2 of 99.8%. Thus, the effect of the strain signal pattern and impact duration with different velocities and thicknesses are correlated with energy from PSD. This suggests that velocity and thickness are important parameters to be considered in testing the material and finally this correlation can be used as an alternative.